Rectenna Solar Cells - Moddel, Garret; Grover, Sachit; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
Rectenna Solar Cells discusses antenna-coupled diode solar cells, an emerging technology that has the potential to provide ultra-high efficiency, low-cost solar energy conversion. This book will provide an overview of solar rectennas, and provide thorough descriptions of the two main components: the diode, and the optical antenna. The editors discuss the science, design, modeling, and manufacturing of the antennas coupled with the diodes. The book will provide concepts to understanding the challenges, fabrication technologies, and materials required to develop rectenna structures. Written by experts in their specialized fields.
Are rectenna solar cells viable? -- Optical frequency rectification -- Efficiency limits for solar spectrum rectification -- Solar and thermal aperture antenna performance limits -- Metal insulator and multi-insulator diodes for rectenna solar cells -- Impact of Tunnel Barrier Dielectric and Roughness on MIM and MIIM Diodes -- Nanoscale Rectenna with Sharp Tips for Absorption and Rectification of Optical Radiation -- A Mid-IR Antenna Integrated with a Geometrically Asymmetrical Metal-Insulator-Metal Rectifying Diode -- Investigation of the infrared radiation detection mechanism for antenna-coupled metal-(oxide)-metal structures -- Geometric diodes for optical rectennas -- Overview of Nano-Antennas for Solar Rectennas -- On the solar energy harvesting efficiency of nano-antennes -- Optical antennas and enhanced nonlinear effects -- Large-Area Fabrication of Antennas and Nanodiodes -- Point-Contact Based MIM Diode Fabrication: A Facile Route for Materials Screening -- Techniques for Roll-to-Roll Manufacturing of Flexible Rectenna Solar Cells -- Thermophotovoltaics: An alternative to and potential partner with rectenna energy harvesters.
Keywords: Energy; Energy systems; Electric power production; Optics; Optoelectronics; Plasmons (Physics).; Microwaves; Optical engineering; Energy; Energy Systems; Microwaves, RF and Optical Engineering; Optics, Optoelectronics, Plasmonics and Optical Devices; Energy Technology; Electronic books